Remembering Your Roots: The Role of Horticulture Therapy in People Living with Dementia - Kelly Reilly Kroustos; Gretchen Horning; Jennifer Gurevich; Anna Gurevich; Kristen Finley Sobota (Ohio Journal of Public Health, 2020)
Introduction: Dementia is a debilitating disease affecting over 50 million people. Major challenges facing patients with dementia lie in the impact of the behavioral and psychological symptoms of dementia (BPSD). The American Geriatrics Society and Dementia Action Alliance recommend against the use of antipsychotics as first-line treatment. Antipsychotics often fail to treat BPSD whereas nonmedication practices such as horticulture therapy may lessen BPSD. Guideline evidence has provided a unique opportunity for public health officials to assist in filling this vital role in the approach to BPSD management. Methods: Several studies and meta-analyses were reviewed to determine the effectiveness of horticulture therapy in managing BPSD, and evidence supports horticulture therapy as an effective method of addressing BPSD. Results: The benefits of horticulture therapy extend beyond addressing only BPSD; through multisensory stimulation, patients have increased physical activity, reduced stress, and improved sleep. Horticulture therapy has been shown to decrease the sense of loss and reestablish the patient in a familiar nurturing role, providing the patient with a sense of purpose. Conclusion: Stakeholders within the public health sector are strategically positioned to implement evidence-based interventions that address the unmet needs for the care of dementia within the community.
Keywords: Dementia; BPSD; Horticulture; Gardening therapy; Nonmedication